Concordance of Posttraumatic Stress Disorder Symptoms Assessed via Retrospective Report Versus Experience Sampling Methods in Community Women Experiencing Intimate Partner Violence. - Kiefer, Reina; Schick, Melissa R.; Newberger, Noam G.; Ferguson, Jewelia J.; Raudales, Alexa M.; Sullivan, Tami P.; Weiss, Nicole H. (Journal of Interpersonal Violence, 2024)
Posttraumatic stress disorder (PTSD) is one of the most prominent negative health consequences that women experiencing intimate partner violence (IPV) may develop. However, research on PTSD among women experiencing IPV has largely relied on retrospective reporting methods, which are vulnerable to bias and may consequently misrepresent PTSD symptoms. This study evaluated the concordance between PTSD symptoms assessed via retrospective self-report and experience sampling methods (ESM), which involve repeated within-day sampling of experiences in near real-time and in natural environments. Community women (N = 134) experiencing IPV (M = 40.7, 30.4% Black) responded to ESM surveys three times a day for 30 days and then completed a follow-up interview. Retrospective self-report of PTSD symptoms, which were assessed during the follow-up interview, were compared to ESM reports of PTSD symptoms. Retrospective reports of PTSD symptoms were significantly different from PTSD symptoms reported during the ESM period, but most closely resembled peak PTSD symptoms. Notably, retrospective reports of PTSD symptoms were significantly different, with a very large effect size, from average PTSD symptoms reported during the ESM period. Discordance scores were significantly negatively associated with the number of days on which any IPV occurred, suggesting that as the frequency of IPV experiences increased, differences between retrospective PTSD symptoms and each ESM symptom pattern decreased. This study provides an important contribution to the literature by highlighting meaningful differences in PTSD symptoms assessed via retrospective self-report versus ESM and the role of IPV context. Findings emphasize the importance of utilizing ESM in PTSD research with women experiencing IPV.